Una clasificación de las zonas rurales de municipios sin predialización catastral - Mutis G., Hernando E. (Revista de Ingeniería, 2003)
The main purpose of this paper is developing and applying a methodology based on multivariate statistical procedures to endorse a classification of certain rural regions in Colombia. In order to achieve the aims, cluster analyses were the basic procedures made. The techniques of principal components, canonical variates, discriminant analysis and Andrews' plots were used to validate the cluster analyses results.